Effects of wood kraft pulp feeding on feed digestibility and rumen fermentation of Japanese Black steer in the middle fattening stage. (27th July 2021) - Mizuguchi, Hitoshi; Maeda, Yuka; Nishimura, Keiko; Shinkura, Hiroshi; Kurosu, Kazuhiro; Terada, Fuminori; Kushibiki, Shiro
Abstract: We investigated the effects of wood kraft pulp (KP) feeding on feed digestibility and rumen fermentation of Japanese Black (JB) steer in the middle fattening stage. The feeding experiment was carried out a replicated 3 × 3 Latin square design using six JB steers (16.2 ± 0.8 months of age). Steers were fed rice straw and three concentrated feeds: commercial formula feed (control), formula feed containing 7.5% KP on a dry matter (DM) basis (7.5% KP), and formula feed containing 15% KP on a DM basis (15% KP). Feed digestibility and rumen fermentation parameters were recorded for 3 days during the measurement period, after an adaptation phase of 11 days. There was no significant difference in DM intake per day among diets. A slightly higher digestibility of neutral detergent fiber was observed in steers fed 15% KP, compared with those fed other diets ( P  = 0.059). The butyric acid ratio in rumen fluid was higher in steers fed KP diets than in steers fed control ( P  = 0.083). The average ruminal pH was unaffected by KP diets. This study suggests that replacing 15% of concentrated feed with KP has little effect on feed digestibility and rumen fermentation in JB fattening steer.